Medicinal and surgical management of tail infections in buffaloes - Patil, Manjunath; Sreedhara, Jajur Narayanashetty; Kumar, Desai Dilip (Buffalo Bulletin, 2020)
A study was conducted in 10 clinical cases of tail infections in buffaloes. Out of 10 buffaloes, 3 were Murrah, 2 each were Pandharpuri and Surti, 1 was Mehsana and 2 were non-descript-, respectively. The age of buffaloes ranged between 5 to 7 years old. Various tail infections were necrosis and gangrene of lower third of the tails and infected wound at tip of the tails, fracture at mid coccygeal region, varicose vein at upper third of the tail, traumatic injury at mid coccygeal region and maggot wound at the base of the tail near anus region. These cases were successfully managed either with conservative therapy or surgery.